Load sharing database in information-analytical system - Жуков, І. А.; Кравець I. М. (Problems of Informatization and Control, 2007)
It Is Created information-analytical system Mintranssvyazi Ukraines, which is intended for extension of the functional possibilities separate information-analytical systems, structured subdivisions, which give a chance buildings of the analytical reports about realization of the tasks for shaping and developments information society in Ukraine. For decision of the task of the distribution data and optimization requests are considered mobile agents and evolution algorithm. The Portioned systems modeling in the manner of column, in which determined vector of the dynamic expenseses. For redistribution given are offered to use the evolution method. Experimental results on system IAS prove efficiency of the offered method